Reducing Crime Through Environmental Design: Evidence from a Randomized Experiment of Street Lighting in New York City - Chalfin, Aaron (Journal of quantitative criminology, 2022)
Objectives This paper offers novel experimental evidence that violent crimes can be successfully reduced by changing the situational environment that potential victims and offenders face. We focus on a ubiquitous but understudied feature of the urban landscape—street lighting—and report the first experimental evidence on the effect of street lighting on crime. Methods Through a unique public partnership in New York City, temporary street lights were randomly allocated to 40 of the city’s public housing developments. Results We find evidence that communities that were assigned more lighting experienced sizable reductions in nighttime outdoor index crimes. We also observe a large decline in arrests indicating that deterrence is the most likely mechanism through which the intervention reduced crime. Conclusion Results suggests that street lighting, when deployed tactically, may be a means through which policymakers can control crime without widening the net of the criminal justice system.